A Review of Douglass C. North, John Joseph Wallis, and Barry R. Weingast'sViolence and Social Orders: A Conceptual Framework for Interpreting Recorded Human History - Bates, Robert (Journal of Economic Literature, 2010)
In Violence and Social Orders: A Conceptual Framework for Interpreting Recorded Human History, Douglass C. North, John Joseph Wallis, and Barry R. Weingast probe the organizational foundations of development. Outlining the properties of the “natural” and “open entry” societies, they highlight as well the conditions under which societies can move from one to the other, thereby achieving political order and economic prosperity.